Characterization of a commonly used mouse model of SMA reveals increased seizure susceptibility and heightened fear response in FVB/N mice - Rocky G. Gogliotti; Cathleen Lutz; Michael Jorgensen; Kimberly Huebsch; Sookyong Koh; Christine J. DiDonato (Neurobiology of Disease, 2011)
The SMN2 transgenic mouse, Tg(SMN2)89Ahmb, has emerged as the most widely used in spinal muscular atrophy (SMA) research. Here we clone the genomic integration site of the transgene and demonstrate it to be in intron 4 of the metabotropic glutamate receptor 7 (mGluR7) gene. We found that the integration of this transgene significantly reduced both mGluR7 mRNA and protein levels (24% and 9%, respectively). To determine if phenotypes associated with mGluR7 knockout mice were present in Tg(SMN2)89Ahmb containing mice, we subjected mice homozygous for the transgene to open field and seizure susceptibility tests. When compared to wild type FVB/N mice, Tg(SMN2)89Ahmbtg/tg mice exhibited significantly longer times in finding a safe wall-adjacent square (+54 s if Smn+/+, +90 s if Smn+/−), as well as a significantly higher frequency of generalized seizure in response to a subthreshold dose of pentylenetrazol (0.11 vs 0.45). These findings aid in explaining the sudden unexpected death that occurs within SMA mouse colonies that contain a homozygous Tg(SMN2)89Ahmb transgene. This should be taken into account in pre-clinical studies that utilize this transgene, especially in therapy-treated SMA mice that have extended survival.